2010
DOI: 10.1103/physrevb.82.024513
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast transient response and electron-phonon coupling in the iron-pnictide superconductorBa(Fe1xCox)

Abstract: The transient response of Ba(Fe1−xCox)2As2, x=0.08 was studied by pump-probe optical reflectivity. After ultrafast photoexcitation, hot electrons were found to relax with two different characteristic times, indicating the presence of two distinct decay channels: a faster one, of less than 1 ps in the considered pump fluence range, and a slower one, corresponding to lattice thermalization and lasting ∼ = 6ps. Our analysis indicates that the fast relaxation should be attributed to preferential scattering of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
103
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 33 publications
10
103
3
5
Order By: Relevance
“…Many have pointed out that the electron-phonon coupling is too weak (by about a factor of 5, Osborn et al, 2009) in these materials to account for the >20 K T c s. Boeri, Dolgov, and Golubov (2008) Rettig et al (2010) found in the 122 parent compound EuFe 2 As 2 , using time resolved ARPES, that el-ph < 0:5 while Mansart et al (2010) (2010a), following the same analysis as used in their FeSe 1Àx isotope effect work, argued that, when adjusted for structural changes, the results of Liu et al and Shirage et al are also consistent with a conventional % 0:35-0:4. Obviously, the possible partial role of the phonons in superconductivity in these materials is still not entirely decided but the evidence from the isotope measurements to date, with the possible exception of the low T c FeSe 1Àx , argues against electron-phonon coupling as the primary pairing mechanism.…”
Section: A Theory Of Superconductivity and Some Relevant Experimentsmentioning
confidence: 99%
“…Many have pointed out that the electron-phonon coupling is too weak (by about a factor of 5, Osborn et al, 2009) in these materials to account for the >20 K T c s. Boeri, Dolgov, and Golubov (2008) Rettig et al (2010) found in the 122 parent compound EuFe 2 As 2 , using time resolved ARPES, that el-ph < 0:5 while Mansart et al (2010) (2010a), following the same analysis as used in their FeSe 1Àx isotope effect work, argued that, when adjusted for structural changes, the results of Liu et al and Shirage et al are also consistent with a conventional % 0:35-0:4. Obviously, the possible partial role of the phonons in superconductivity in these materials is still not entirely decided but the evidence from the isotope measurements to date, with the possible exception of the low T c FeSe 1Àx , argues against electron-phonon coupling as the primary pairing mechanism.…”
Section: A Theory Of Superconductivity and Some Relevant Experimentsmentioning
confidence: 99%
“…IV G, the electron-phonon mechanism appears to be too weak to give rise to the high T c values observed in the Fe-based superconductors. 274,461,[485][486][487][488] The proximity of the superconducting compositions to those with long-range antiferromagnetic/spin density wave order suggests that an electronic mechanism might be responsible that involves the exchange of antiferromagnetic spin fluctuations. Indeed, the experimental evidence is strong that the highest-T c Fe-based superconductors are spin singlet, s ± -wave superconductors with this superconducting mechanism.…”
mentioning
confidence: 99%
“…Therefore, understanding of couplings among those instabilities is essential to unveil the mechanism of HTSC. Various ultrafast techniques have revealed coherent lattice vibrations that strongly modulate the properties of Fe-based superconductors [1,2,[7][8][9][10][11][12]. Although the electron-phonon coupling (EPC) on its own fails to account for the large gap and the high superconducting transition temperature, it is still considered as one of the important ingredients for the paring possibly in conjunction with the magnetic interaction [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%